2022
DOI: 10.1177/09504222211070950
|View full text |Cite
|
Sign up to set email alerts
|

Who they are versus what they want: How dominance, influence, steadiness, and compliance profiles can aid in developing employability

Abstract: This paper draws attention to a behavior-based assessment instrument that is frequently utilized in industry settings but less utilized in the academic classroom. The authors argue that this instrument, the dominance, influence, steadiness, and compliance (DISC) profile, can be useful in training and developing soft skills desired by employers. They also examine the effects of gender and work experience on the various DISC patterns to better understand how this instrument may be useful for coaching and mentori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 40 publications
(53 reference statements)
1
2
0
Order By: Relevance
“…Results indicate that individuals do not consider motivation to be the responsibility of individual team members. Although somewhat unexpected, this is consistent with findings by Fertig et al (2022) in which undergraduate students exhibited higher compliance competencies than working graduate students, presumably due to learned conformance to expectations in academic classrooms.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Results indicate that individuals do not consider motivation to be the responsibility of individual team members. Although somewhat unexpected, this is consistent with findings by Fertig et al (2022) in which undergraduate students exhibited higher compliance competencies than working graduate students, presumably due to learned conformance to expectations in academic classrooms.…”
Section: Discussionsupporting
confidence: 86%
“…Students’ PCs focused more on implicit and non-promissory expectations of educational experiences versus promises that make up PCs in the employment context. And Fertig et al (2022) found interesting gender and experience differences related to behavioral competencies developed among working graduate students compared to those of undergraduate students.…”
Section: Limitationsmentioning
confidence: 97%
See 1 more Smart Citation